Spatiotemporal control of mitotic exit during anaphase by an aurora B-Cdk1 crosstalk - Olga Afonso; Colleen M Castellani; Liam P Cheeseman; Jorge G Ferreira; Bernardo Orr; Luisa T Ferreira; James J Chambers; Eurico Morais-de-Sá; Thomas J Maresca; Helder Maiato (eLife, 2019)
According to the prevailing ‘clock’ model, chromosome decondensation and nuclear envelope reformation when cells exit mitosis are byproducts of Cdk1 inactivation at the metaphase-anaphase transition, controlled by the spindle assembly checkpoint. However, mitotic exit was recently shown to be a function of chromosome separation during anaphase, assisted by a midzone Aurora B phosphorylation gradient - the ‘ruler’ model. Here we found that Cdk1 remains active during anaphase due to ongoing APC/CCdc20- and APC/CCdh1-mediated degradation of B-type Cyclins in Drosophila and human cells. Failure to degrade B-type Cyclins during anaphase prevented mitotic exit in a Cdk1-dependent manner. Cyclin B1-Cdk1 localized at the spindle midzone in an Aurora B-dependent manner, with incompletely separated chromosomes showing the highest Cdk1 activity. Slowing down anaphase chromosome motion delayed Cyclin B1 degradation and mitotic exit in an Aurora B-dependent manner. Thus, a crosstalk between molecular ‘rulers’ and ‘clocks’ licenses mitotic exit only after proper chromosome separation.